2005
DOI: 10.1103/physrevlett.95.076001
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Particle Dynamics Simulations of Polymer Chains: Scaling Laws and Shearing Response Compared to DNA Experiments

Abstract: Dissipative particle dynamics simulations of several bead-spring representations of polymer chains in dilute solution are used to demonstrate the correct static scaling laws for the radius of gyration. Shear flow results for the wormlike chain simulating single DNA molecules compare well with average extensions from experiments, irrespective of the number of beads. However, coarse graining with more than a few beads degrades the agreement of the autocorrelation of the extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 19 publications
4
98
0
Order By: Relevance
“…The polymer in a good solvent shows satisfactory agreement with scaling and Kirkwood theory, and the polymer melt is in excellent agreement with the predictions of Rouse theory. Symeonidis et al [128] demonstrated the correct static scaling laws for the radius of gyration by DPD simulations of several beadspring representations of polymer chains in dilute solution. They found that the worm-like chain simulating single DNA molecules compares well with average extensions in shear flow from experiments.…”
Section: Movement and Suspension Of Macromolecules Inmentioning
confidence: 99%
“…The polymer in a good solvent shows satisfactory agreement with scaling and Kirkwood theory, and the polymer melt is in excellent agreement with the predictions of Rouse theory. Symeonidis et al [128] demonstrated the correct static scaling laws for the radius of gyration by DPD simulations of several beadspring representations of polymer chains in dilute solution. They found that the worm-like chain simulating single DNA molecules compares well with average extensions in shear flow from experiments.…”
Section: Movement and Suspension Of Macromolecules Inmentioning
confidence: 99%
“…In particular, Symeonidis et al [13] used additional intramolecular interactions (e.g. Lennard-Jones-like repulsion term) to increase the chain selfavoidance and experimented with different forms of the bond springs (i.e.…”
Section: Previous Simulationsmentioning
confidence: 99%
“…of equation (1) form) hold in the case of the DPD-based simulations. This issue was partly considered in [10][11][12][13][14]. However, some issues remain unclear (see the next section 2 for details).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, new forces (elastic, rigid, etc.) can be added between particles in order to describe long polymers [71][72][73][74] , rigid or deformable particles in suspension [75] , porous media [76] , droplets [77] , cells [78][79][80] , or even more complex thixotropic materials [81] (see Fig. 1).…”
Section: How Is the Fluid Complexity Incorporated In Sdpd?mentioning
confidence: 99%